Advances in the Characterisation and Remediation of Sites Contaminated with Petroleum Hydrocarbons - García-Rincón, Jonás; Gatsios, Evangelos; Lenhard, Robert J.; Atekwana, Estella A.; Naidu, Ravi (Environmental Contamination Remediation and Management, 2024)
This open access book synthesizes important advances in the assessment and management of soil and groundwater systems contaminated with petroleum hydrocarbons, especially in the form of light non-aqueous phase liquids (LNAPLs). LNAPL characterization and remediation is challenging due to the multi-phase, multi-component nature of the problem and the various physical, chemical, and biological processes involved in a dynamic and heterogeneous hydrogeological setting. This book focuses on the current state of practice of LNAPL characterization and remediation and seeks to provide information and a framework that would allow some of these complexities to be better addressed by contaminated land practitioners, researchers, and regulators.